The Bible with or without Jesus how Jews and Christians read the same stories differently - Levine, Amy-Jill 1956-; Brettler, Marc Zvi 1958- (San Francisco HarperOne, 2020)
"The editors of The Jewish Annotated New Testament, Amy-Jill Levine and Marc Brettler, explore how Jews and Christians can learn from and understand each other better by exploring how they read many of the same Bible stories through different lens"--
Keywords: Bible -- Criticism, interpretation, etc; Bible -- Criticism, interpretation, etc; Judaism -- Relations -- Christianity; Christianity and other religions -- Judaism